1994
DOI: 10.1007/bf02816125
|View full text |Cite
|
Sign up to set email alerts
|

Excitotoxicity

Abstract: Neurochemical observations on cortical biopsies form 48 patients under surgical treatment for pharmacoresistant partial epilepsy showed a 70-80% increase in glutamate concentration when expressed in relation to neuron specific enolase. Intraperitoneal administration of one of its receptor agonists, kainic acid (KA), to the rat led to increased epileptogenic activity of the limbic type in a dose-dependent fashion. The KA injection also led to a neuronal cell death and a gliosis, closely correlated to the extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Our results suggest increased glutamate in the CSF of PKC patients could lead to neuronal hyperexcitability. In fact, high extracellular glutamate concentrations in the brain have been identified as a likely trigger of epileptic seizures in mesial temporal lobe epilepsy (MTLE) [ 13 , 28 ]; these might be associated with decreased hippocampal volumes [ 29 ]. By studying genetic absence epilepsy rats from Strasbourg (GAERS), Sirvanci et al [ 30 ] found that the glutamate density in the CA3 region of GAERS hippocampus was significantly increased compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest increased glutamate in the CSF of PKC patients could lead to neuronal hyperexcitability. In fact, high extracellular glutamate concentrations in the brain have been identified as a likely trigger of epileptic seizures in mesial temporal lobe epilepsy (MTLE) [ 13 , 28 ]; these might be associated with decreased hippocampal volumes [ 29 ]. By studying genetic absence epilepsy rats from Strasbourg (GAERS), Sirvanci et al [ 30 ] found that the glutamate density in the CA3 region of GAERS hippocampus was significantly increased compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SNAP25 plays an important role in the regulation of excitatory amino acids (EAAs) neurotransmitter release. The dysfunction of EAA transmission, especially glutamate transmission, plays a role in many nervous diseases, including epilepsy, migraines and children with high functioning autism [ 13 , 14 , 15 ]. A recent high-resolution proteomics analysis offered another important clue into the function of PRRT2.…”
Section: Introductionmentioning
confidence: 99%
“…25 Elevated extracellular glutamate levels have also been reported in animal models of epilepsy and epilepsy patients alike, particularly in individuals with temporal lobe epilepsy. [26][27][28][29] EAAT2 p.Gly82Arg (subject A) substitutes a small hydrophobic and neutrally charged glycine with hydrophilic, positively charged arginine within the cytoplasmic loop joining the first pair of transmembrane domains ( Figure 1). The same substitution is reported in the Epi4K-EPGP dataset in a subject with infantile spasms 4 and two additional individuals with a severe EE, and de novo variants (EAAT2 p.Gly82Arg and p.Leu85Pro) were reported 33 during the preparation of this manuscript.…”
mentioning
confidence: 99%
“…The glutamate levels are directly correlated with the occurrence of epilepsy. Elevated glutamate levels have been reported in human brain tissues and animal models of epilepsy 22 . During the seizure period, glutamate levels increased to approximately 10 times their normal values, and then gradually returned to normal when a seizure has ceased 23 .…”
Section: Discussionmentioning
confidence: 99%